2020
DOI: 10.1097/md.0000000000020274
|View full text |Cite
|
Sign up to set email alerts
|

STAPLAg: a convenient early warning score for use in infected patients in the intensive care unit

Abstract: Sepsis is a life-threatening disease in the intensive care unit (ICU). The current diagnostic criteria for sequential organ failure assessment (SOFA) scores do not reflect the current understanding of sepsis. We developed a novel and convenient score to aid early prognosis. Retrospective multivariable regression analysis of 185 infected emergency ICU (EICU) patients was conducted to identify independent variables associated with death, to develop the new “STAPLAg” score; STAPLAg was then validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Hypernatremia can be an independent predictor of poor outcome in septic patients in the ICU, which is similar to some views [38]. However, another study [39] showed the risk of death increased by 71.6% when serum sodium was < 129 mmol/L for patients with sepsis. Lactate and AG are typical metabolic indicators.…”
Section: Discussionsupporting
confidence: 81%
“…Hypernatremia can be an independent predictor of poor outcome in septic patients in the ICU, which is similar to some views [38]. However, another study [39] showed the risk of death increased by 71.6% when serum sodium was < 129 mmol/L for patients with sepsis. Lactate and AG are typical metabolic indicators.…”
Section: Discussionsupporting
confidence: 81%
“…It was also confirmed in patients with sepsis and severe COVID-19 [ 29 , 30 ]. The parameters of the predicted score established in the authors’ study in 2020 overlap with these indicators [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because sepsis is caused by a disordered host response to infection, biomarkers related to immune dysfunction have received attention in the study of sepsis in recent years [ 10 ]. In 2019, the authors established the STAPLAg scoring system, which can be used to predict the occurrence of sepsis and subsequent death using six clinical indicators related to the host’s infection and immune status (sodium concentration, troponin I concentration, albumin [ALB] concentration, platelet count [PTL]/lymphocyte ratio, lactate concentration, and age) [ 11 ]. Still, the model is not perfect and can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoalbuminemia can lead to weakened immunity and increased susceptibility to infectious diseases, and patients with sepsis have complex pathophysiological conditions, including immune imbalance and disorders of biosynthesis and catabolism [15]. Furthermore, hypoalbuminemia was found to be an independent predictor of fatal sepsis in an intensive care unit, with a 75.2% increase in the mortality rate among patients with serum albumin <2.9 g/dL [16]. Serum albumin levels are associated with the prognosis of pneumonia, severe sepsis, and bacteremia [17,18].…”
Section: Discussionmentioning
confidence: 99%